Pengaruh Inflasi dan Tingkat Suku Bunga terhadap Market Share dengan Dana Pihak Ketiga Sebagai Variabel Intervening pada Bank Syariah di Indonesia: Studi Kasus Bank Umum Syariah di Indonesia Periode 2017-2021 - Ritonga, Mayang Sari; Arif, Muhammad; Ja, Nurul (As-Syirkah: Islamic Economic & Financial Journal, 2023)
This study aims to analyze or determine the effect of inflation and interest rates on market share with third party funds as intervening variables in Islamic banks in Indonesia (Case Study of Islamic Commercial Banks for the 2017-2021 Period). The population used is all Islamic Commercial Banks in Indonesia and registered with the OJK for the 2017-2021 period. Using a saturated sample technique, namely monthly reports of Islamic Commercial Banks in Indonesia for the 2017-2021 period. The type of data used is secondary data. The data analysis technique used in this study using SPSS 20 consists of Descriptive Statistical Analysis, Classical Assumptions Test, Hypothesis, Multiple Regression Analysis, and Path Analysis Test. The results of this study indicate that: (1) Inflation has a negative effect on market share (2) Interest rates have an effect on market share. (3) Inflation has a significant effect on Market Share through Third Party Funds. (4) Interest rates have no effect on market share through DPK. (5) Inflation and interest rates have a positive and significant effect on market share simultaneously. (6) Inflation and interest rates have a significant effect on market share through third party funds.